Sliding Window: The Impact of Trace Size in Anomaly Detection System for Containers Through Machine Learning - Castanhel, Gabriel Ruschel; Heinrich, Tiago; Ceschin, Fabrício; A. Maziero, Carlos (Anais da Escola Regional de Redes de Computadores (ERRC); 2020: Anais da XVIII Escola Regional de Redes de ComputadoresDO - 10.5753/errc.2020.15203, 2020)
Anomaly intrusion detection in Host-based Intrusion Detection System (HIDS) is a process intended to monitor operations on a host to identify behaviors that differ from a “normal ” system behavior. System call based HIDS uses traces of calls to represent the behavior of a system. Due to the volume of data generated by applications and the operating system, sliding windows are applied in order to asses an online environment, allowing intrusions to be detected in real time while being still executed. The respective study explores the impact that the size of the observation window has on Machine Learning (ML) one-class algorithms.